Renal lithiasis from a nephrologist’s perspective - Serra, A (2019)
Man has known urinary lithiasis since antiquity. In Portuguese medicine, this is a pathology seen predominantly from the urology perspective, but renal lithiasis is evaluated and treated preventively by nephrologists worldwide, and its study has contributed significantly to knowledge of how the renal tubule works. Nephrolithiasis is a relatively common disease in the adult population and, in Portugal, is observed in about 7.3% of the population. The main pathophysiological mechanisms of the most frequent types of kidney stones and who and how to conduct the metabolic research are briefly described. Medical treatment is also addressed, keeping in mind that nephrolithiasis is often accompanied by extra-renal manifestations that should be investigated and treated, namely arterial hypertension, obesity, diabetes mellitus and osteo-metabolic disease.